The Effect of Motivational Interviewing on Despair, Motivation and Medication Compliance for Tuberculosis Patients - Zuliani Zuliani (Indonesian Journal of Health Research, 2019)
Introduction. Tuberculosis (TB) is an infectious disease that can attack various organs, especially the lung caused by Mycobacterium tuberculosis. The use of the Directly Observed Treatment Short-course (DOTS) strategy for tuberculosis treatment has not been successful, while cases of multidrug tuberculosis resistance have increased. Long-term treatment leads to decreased motivation and despair to recover. Motivational interviewing (MI) intervention is one way to overcome them. The purpose of this study was to determine the effect of motivational interviewing on hopelessness, motivation, and adherence to taking medication for tuberculosis patients. Methods. Pre experiment with the form of pretest - posttest group design was used in this study. The research sample amounted to 18 respondents by means of random sampling technique. This intervention was carried out for four weeks with two meetings per week. The independent variable is motivational interviewing, while the dependent variable is hopelessness, motivation, and compliance with taking medication. The instrument in this study uses a questionnaire that has been tested for validity and reliability. Statistical tests using the Wilcoxon signed rank test. Results. The results of statistical tests showed that motivational interviewing had an effect on decreased despair (p = 0,000) and increased motivation and compliance with medication (p = 0,000). Conclusion. Motivational interviewing interventions help tuberculosis sufferers identify, evaluate and respond to something they think, so that motivational interviewing has an effect on decreasing hopelessness, increasing motivation and adhering to medication in tuberculosis patients.